Optical Feedback Linear Cavity Ringdown Spectroscopy - Wang, Xingping; Zhao, Gang; Jiao, Kang; Chen, Bing; Kan, Ruifeng; Cong, Zhenhua; Liu, Jianguo; Ma, Weiguang (Frontiers in Physics, 2022)
Optical feedback cavity ringdown spectroscopy is presented with a linear Fabry-Pérot cavity and a cost-effective DFB laser. To circumvent the low coupling efficiency caused by the broad laser linewidth, optical feedback technique is used and an enhanced coupling efficiency of 31%, mainly limited by impedance mismatch and mode mismatch, is obtained. The trigger of the ringdown event is realized by the shutoff of the laser driving current, and a novel method with the aid of one electronic switch is applied to avoid the ringdown events excited by the unexpected cavity modes during the process of laser current recovery. As a result, the ringdown signal with a signal-to-noise ratio of 2500 is achieved. Through continuous monitoring, the fractional uncertainty of the empty cavity ringdown times is assessed to be 0.04%. An Allan variance analysis indicates a detection sensitivity of 4.3×10-10 cm-1 is resulted at an integration time of 120 s, even with a moderate finesse cavity. To further improve the long-term stability, we regularly rectify the empty cavity ringdown time and an improvement factor of 2.5 is demonstrated.